نحو نموذج تكاملي لتعزيز الرضا عن صورة الجسم: تحليل نقدي وبناء إطار مفاهيمي متعدد الأبعاد (Comprehensive Journal of Science, 2025)
This research aims to address the critical gap in body image satisfaction literature by developing an integrative multidimensional model that transcends the limitations of single-approach frameworks. The study aims to critically analyze prevailing psychological models (cognitive-behavioral, psychoanalytic, and humanistic-existential) and construct a comprehensive theoretical framework tailored to Arab, specifically Libyan, cultural contexts. Employing a conceptual synthesis methodology, the research examines theoretical foundations and empirical evidence from 56 studies spanning 2010-2025. Through systematic comparative analysis, the study reveals that body image satisfaction constitutes a dynamic psychological construct encompassing cognitive-affective, unconscious-symbolic, existential-meaning, and sociocultural dimensions. Findings indicate that fragmented theoretical approaches demonstrate limited effectiveness when applied independently, particularly within Arab societies where cultural values, religious beliefs, and social gender expectations significantly shape body perception. The proposed integrative model operates through functional synergy across four interconnected levels: structural-dynamic (psychoanalytic roots), cognitive-affective (thought modification), value-existential (meaning reconstruction), and contextual-cultural (environmental framing). The research recommends implementing culturally adapted therapeutic interventions, developing specialized training programs for mental health practitioners, and conducting experimental validation studies. This framework offers practical implications for clinical practice and counseling services while respecting indigenous cultural specificities and advancing culturally responsive psychological interventions.
Keywords: Body Image Satisfaction, Integrative Psychological Model, Multidimensional Framework, Cultural Adaptation, Arab Context